2016
DOI: 10.1093/jxb/erw095
|View full text |Cite
|
Sign up to set email alerts
|

Phylogenetic tree-informed microRNAome analysis uncovers conserved and lineage-specific miRNAs inCamelliaduring floral organ development

Abstract: In plants, miRNAs are endogenous small RNAs derived from single-stranded precursors with hairpin structures. The evolution of miRNAs and their targets represents one of the most dynamic circuits directing gene expression, which may play fundamental roles in shaping the development of distinct plant organs. Here we performed high-throughput small RNA sequencing in five organ types of Camellia azalea to capture the spatial profile of small non-coding RNA. In total we obtained >227 million high-quality reads and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
25
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(28 citation statements)
references
References 55 publications
3
25
0
Order By: Relevance
“…In Arabidopsis , SPL was found to be required for anther sporogenic tissues differentiation and expressed abundantly in the anther tissues 17, 32, 33 . In Camellia , miR156 was expressed abundantly in stamen where SPL1 and SPL2 were expressed at a low level 22 . In this study, SPLs were expressed just in stamen filaments but not anther tissues (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In Arabidopsis , SPL was found to be required for anther sporogenic tissues differentiation and expressed abundantly in the anther tissues 17, 32, 33 . In Camellia , miR156 was expressed abundantly in stamen where SPL1 and SPL2 were expressed at a low level 22 . In this study, SPLs were expressed just in stamen filaments but not anther tissues (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…For each small RNA sequencing library, the clean reads range from 18–30 bp were obtained and then filtered through RNA databases before miRNA identification 22 . The transcriptome assemble from C. japonica was used as reference for precursors identification.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, we also determined the frequency of the base of the mature miRNAs, the result showed that the 20bp, 21bp, and 22bp miRNAs preferentially start with 'U' at the rst base (46.96%, 55.37%, and 61.22%, respectively) (Additional le 1: Fig.S3), while 24bp miRNAs preferred 'A' (58.5%). Comparing with miRNA's rst nucleotide bias analysis in other species, we found the bias tendency in 21bp, 22bp and 24bp miRNAs is similar to Camellia japonica [34], pomegranate [35].…”
Section: Identi Cation Of Micrornas In the New Lotus Reference Genomementioning
confidence: 55%
“…MiRNA was first identified in Caenorhabditis elegans and subsequently found in almost all eukaryotes [9]. In higher plants, miRNAs play important roles in different developmental stages by mediating gene silencing at transcriptional and post-transcriptional levels [10,11] and appear to be one of the most significant regulatory mechanisms [12][13][14]. Increasing evidence indicates that miRNAs are involved in plant development, signaling, abiotic stresses, and symbiotic relationship regulation [15,16].…”
Section: Introductionmentioning
confidence: 99%